Hyponatremia as a Prognostic Factor in Heart Failure: A Narrative Review - Gawron, Natalia; Jurkowski, Filip; Bojanowski, Hubert Tomasz; Czmyr, Jędrzej; Sito, Maksymilian; Marczak, Zuzanna; Dobracka, Aleksandra; Zachar, Kinga; Jarowicz, Monika; Wójcik, Łukasz (Journal of Education, Health and Sport, 2026)
Introduction and purpose: Hyponatremia is the most frequent electrolyte abnormality in heart failure (HF) and reflects neurohormonal activation, congestion, renal dysfunction, and treatment intensity. This narrative review assesses whether hyponatremia is only a marker of advanced HF or an independent prognostic factor, and summarizes its value for risk stratification. Brief description of the state of knowledge: Across acute and chronic HF cohorts, low serum sodium at admission is consistently associated with longer hospitalization, higher in-hospital mortality, greater post-discharge mortality, and more frequent rehospitalization. Prognostic relevance is also seen for persistent hyponatremia, discharge hyponatremia, hospital-acquired hyponatremia, and worsening sodium trajectories during admission. These associations are present in both reduced and preserved ejection fraction and become stronger when hyponatremia coexists with renal dysfunction, severe congestion, or elevated natriuretic peptides. Cohort studies suggest that sodium improvement during hospitalization is linked to better short-term outcomes, but randomized evidence shows that sodium correction alone does not lower mortality. Summary (conclusions): Hyponatremia should be considered a readily available, low-cost prognostic marker in HF rather than an isolated laboratory abnormality. Its value is greatest when interpreted together with congestion, kidney function, and natriuretic peptide burden. Persistent or hospital-acquired hyponatremia identifies particularly vulnerable patients who may benefit from closer monitoring, careful volume reassessment, and optimized guideline-directed therapy. Future studies should determine whether phenotype-guided correction strategies can improve hard clinical outcomes.